2017
DOI: 10.3390/ijms18030553
|View full text |Cite
|
Sign up to set email alerts
|

A New Oleanolic Acid Derivative against CCl4-Induced Hepatic Fibrosis in Rats

Abstract: A novel hepatoprotective oleanolic acid derivative, 3-oxours-oleana-9(11), 12-dien-28-oic acid (Oxy-Di-OA), has been reported. In previous studies, we found that Oxy-Di-OA presented the anti-HBV (Hepatitis B Virus) activity (IC50 = 3.13 µg/mL). Remarkably, it is superior to lamivudine in the inhibition of the rebound of the viral replication rate. Furthermore, Oxy-Di-OA showed good performance of anti-HBV activity in vivo. Some studies showed that liver fibrosis may affiliate with HBV gene mutations. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Daily intraperitoneal administration of Oxy‐Di‐OA (14‐28 mg/kg, ip for 11 weeks) prevented the development of chronic CCl 4 (9 weeks)‐induced liver fibrosis, as evidenced by histology and immunohistochemistry analysis. Oxy‐Di‐OA also decreased the expression of TGF‐β1 . Taken together, OA is beneficial against CCl 4 ‐induced chronic fibrosis and cirrhosis.…”
Section: Low Doses Of Oa Protect Against Hepatotoxicity Induced By a mentioning
confidence: 75%
See 1 more Smart Citation
“…Daily intraperitoneal administration of Oxy‐Di‐OA (14‐28 mg/kg, ip for 11 weeks) prevented the development of chronic CCl 4 (9 weeks)‐induced liver fibrosis, as evidenced by histology and immunohistochemistry analysis. Oxy‐Di‐OA also decreased the expression of TGF‐β1 . Taken together, OA is beneficial against CCl 4 ‐induced chronic fibrosis and cirrhosis.…”
Section: Low Doses Of Oa Protect Against Hepatotoxicity Induced By a mentioning
confidence: 75%
“…Oxy-Di-OA also decreased the expression of TGF-β1. 55 Taken together, OA is beneficial against CCl 4 -induced chronic fibrosis and cirrhosis.…”
Section: Oa Protects Against Chronic Liver Injury Fibrosis and Cirmentioning
confidence: 98%
“…[ 12 ]. Due to its favorable properties, OA is considered as a base molecule for further synthetic modifications to develop lead compounds for hepatoprotective agents in our reported studies and others [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ], and some of these derivatives have been therapeutic candidates in clinical trials [ 20 ]. However, there are some shortcomings in poor water-solubility, low bioavailability, and weak bioactivity, which seriously restrict their further clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Hallmarks of clinical liver injury will be presented in the Special Issue “Molecular Research on Drug Induced Liver Injury” published in the International Journal of Molecular Sciences to address the progress and current standing in the vast field of liver injury. A total of 10 reviews and original articles [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ] have been published in this Special Issue, as detailed in Table 1 .…”
mentioning
confidence: 99%
“…In another experimental study carried out in rats, Xiang et al [ 10 ] reported on the effects of a novel oleanolic acid derivative Oxy-Di-AO on CCl 4 -induced hepatic fibrosis. As a derivative of the hepatoprotective oleanolic acid originally from Ligustrum lucidum , the synthetic Oxy-Di-AO has a protective effect and prevented the development of CCl 4 -induced liver fibrosis when given intraperitoneally daily for 9 weeks.…”
mentioning
confidence: 99%